Design of Enhanced Gain Multiband Minuaturized Antenna for Mobile Communications (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Antennas are the heart of modern communication systems. The response of communication system depends on Antenna. Amongst all the antennas, microstrip antennas are broadly used due to their small size and minimal cost. To function microstrip antenna in various chosen frequencies, slots were being made on patch of different shapes and positions. Including Metamaterial technology in antenna design, reduces the actual dimensions of antenna. In this paper a rectangular shaped patch antenna is designed at 2.4GHz frequency and a rectangular slot of 2.5mmx3.5mm is made on the patch, to operate the antenna at 8 different frequency bands 2.4GHz-2.6GHz, 3.4GHz-3.55GHz, 4.2GHz-4.75GHz, 5.2GHz-5.8GHz, 6.1GHz-6.8GHz, 7GHz-7.3GHz, 7.8GHz-8.2GHz, 9.1GHz-10GHz. Square shaped slots were made on the edges of the patch in three iterations and observed the Gain improvement as the increase in number of iterations. In the first iteration, four slots were made on the edges of the patch and observed the Gain increased from 1.78 dB to 1.82dB.  In second iteration 12 slots were made on the edges of patch and observed the enhancement of Gain to 1.92dB. In third iteration 18 slots were made on edges of patch and observed the Gain improved to 2.04dB. In all the iterations, it was observed that electrical length of patch is gradually reduced, resulting in reduction of size of Antenna. The novelty of the antenna design in this paper is as electrical length of patch is decreased, Gain of the Antenna is increased, exhibiting same operating frequency bands at all the iterations. The proposed multiband miniaturized Antenna can be used for mobile communications covering Bluetooth, Wi-Fi, WIMAX, VOLTE and 5G bands.